2019
DOI: 10.7555/jbr.32.20170137
|View full text |Cite
|
Sign up to set email alerts
|

Emerging pathways of communication between the heart and non-cardiac organs

Abstract: The breakthrough discovery of cardiac natriuretic peptides provided the first direct demonstration of the connection between the heart and the kidneys for the maintenance of sodium and volume homeostasis in health and disease. Yet, little is still known about how the heart and other organs cross-talk. Here, we review three physiological mechanisms of communication linking the heart to other organs through: i) cardiac natriuretic peptides, ii) the microRNA-208a/mediator complex subunit-13 axis and iii) the matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…In a study of 171 healthy British Bangladeshi adults, vitamin D levels were inversely correlated with circulating MMP-9 levels [ 96 ], while a vitamin D metabolite (1α,25(OH) 2 D 3 ) was found to inhibit MMP-9 gene expression, secretion, and activity in the setting of various respiratory infections [ 97 ]. These data suggest possible links between MMP-9 and lipid metabolism in COVID-19, which is not surprisingly based on previous (COVID-19-unrelated) studies by many investigators including our group (for MMP-2, MMP-7, and MMP-9, as well as their tissue inhibitors TIMP-2 and TIMP-3) [ 14 , 78 , 98 , 99 , 100 , 101 , 102 , 103 ].…”
Section: Mmp-involvement In Organ Damage Warrants Investigationsupporting
confidence: 75%
See 1 more Smart Citation
“…In a study of 171 healthy British Bangladeshi adults, vitamin D levels were inversely correlated with circulating MMP-9 levels [ 96 ], while a vitamin D metabolite (1α,25(OH) 2 D 3 ) was found to inhibit MMP-9 gene expression, secretion, and activity in the setting of various respiratory infections [ 97 ]. These data suggest possible links between MMP-9 and lipid metabolism in COVID-19, which is not surprisingly based on previous (COVID-19-unrelated) studies by many investigators including our group (for MMP-2, MMP-7, and MMP-9, as well as their tissue inhibitors TIMP-2 and TIMP-3) [ 14 , 78 , 98 , 99 , 100 , 101 , 102 , 103 ].…”
Section: Mmp-involvement In Organ Damage Warrants Investigationsupporting
confidence: 75%
“…However, MMPs are mediators of tissue and organ damage when their activity is pathologically elevated, as demonstrated by earlier research for MMPs in comorbidities that accompany severe COVID-19 cases [ 1 , 10 , 11 ]. In response to infection with SARS-CoV-2 (and possibly other pathogens), the host’s immune and target cells are likely to release MMPs because one of the physiological stimuli that cause all cells to alter their production and release MMPs is inflammation, which itself is modulated by the MMP-mediated cleavage of cytokines and chemokines [ 25 , 26 , 29 , 76 , 77 , 78 , 79 ]. SARS-CoV-2 infection and the comorbidities that accompany COVID-19 are pro-inflammatory on their own, and their superimposition exacerbates inflammation.…”
Section: Mmp-involvement In Organ Damage Warrants Investigationmentioning
confidence: 99%
“…35 The mechanisms that underlie regulation of systemic metabolism by the cardiac mediator remain elusive but may involve the ability of the heart to modulate lipid metabolism in noncardiac organs such as the liver through the matrix metalloproteinase 2/C-C motif chemokine ligand 7/ cardiac secretory phospholipase A2 axis. 36,37 The myocardium also produces various microRNAs and humoral factors that have the potential to affect systemic metabolism, for example, the natriuretic peptide family of proteins and growth-differentiating factors. 37,38 Modulation of the autonomic nervous system by the cardiac afferent reflex represents another mechanism that can mediate the effect of the heart on metabolism.…”
Section: Vascular Effects On Metabolismmentioning
confidence: 99%
“…36,37 The myocardium also produces various microRNAs and humoral factors that have the potential to affect systemic metabolism, for example, the natriuretic peptide family of proteins and growth-differentiating factors. 37,38 Modulation of the autonomic nervous system by the cardiac afferent reflex represents another mechanism that can mediate the effect of the heart on metabolism. [39][40][41][42][43] This possibility is supported by several studies implicating sympathetic traffic in heart failure-associated cachexia caused by excess loss of adiposity.…”
Section: Vascular Effects On Metabolismmentioning
confidence: 99%
“…Most likely, the best described cardiac endocrine factor is the atrial natriuretic peptide (ANP), the expression of which is increased after myocardial stretching ( Hardy-Rando and Fernandez-Patron, 2019 ). A previous study reported that upon corticosterone stimulation, astrocytes release “ANPergic vesicles” (vesicles enriched in ANP) ( Chatterjee and Sikdar, 2013 ).…”
Section: Inter-organ Crosstalkmentioning
confidence: 99%